2013
DOI: 10.1080/02692171.2012.752445
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corruption on FDI: is MENA an exception?

Abstract: The eruption of the Arab Spring in Tunisia and Egypt was ensued by deterioration in FDI inflows. Whether a new Middle East free of corruption accompanying previous dictatorships will offset the negative ramifications of the uprisings and enhance FDI in the long run remains debatable. Since the evidence on the causal relationship between corruption and FDI is inconclusive, this study attempts to take another step. The paper investigates the link between corruption and FDI flows to the Middle East and North Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 20 publications
5
74
2
10
Order By: Relevance
“…Though, the findings of these studies were significant unlike the results of this research. On the other hand, the results of this research contradict with the findings of Huang (2016), Elfakhani and Mackie (2015), Helmy (2013) and Drury et al (2006). The results of these studies differ from what this research has empirically found due to the fact that the subject of the research covers only BRIC countries which are dissimilar to the countries covered in those researches.…”
Section: Research Findingscontrasting
confidence: 57%
See 1 more Smart Citation
“…Though, the findings of these studies were significant unlike the results of this research. On the other hand, the results of this research contradict with the findings of Huang (2016), Elfakhani and Mackie (2015), Helmy (2013) and Drury et al (2006). The results of these studies differ from what this research has empirically found due to the fact that the subject of the research covers only BRIC countries which are dissimilar to the countries covered in those researches.…”
Section: Research Findingscontrasting
confidence: 57%
“…Thus, the result of the study cannot be applied to situations beyond that period of time. Also, the case of MENA is an exception as a study has empirically demonstrated that there is a positive association between corruption and FDI inflows in the region which could be explained by two main reasons (Helmy, 2013). Firstly, the economic benefits to the foreign investors could out pass the additional costs incurred because of corruption in the area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is some evidence, especially in developing countries, that countries should improve the overall business climate, including improving policies, laws, and regulation related to entrepreneurship and investments, as well as reducing administrative barriers and corruption to attract FDI (Bénassy-Quéré et al, , Assunção et al, 2011Saidi et al, 2013;Staats et al, 2012). On the other side, several empirical research show the opposite results especially regarding corruption level (Helmy, 2013;Bellos et al, 2011) or find institutional factors as statistically insignificant determinants for attracting FDI flows (Bayar et al, 2016;Abdella et al, 2017). It is important to point out that FDI determinants can change over time and theories need to be re-examined (Eicher et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Macroeconomic determinants include the market size, the ratio of government expenditures (Mohamed & Sidiropoulos, 2010), and the current account of the balance of payments (Van Wyk & Lal, 2010). Inward FDI in MENA region is positively influenced by the level of GDP (Aysan et al, 2009;Moosa, 2009), and GDP per capita (Helmy, 2013;Rogmans & Ebbers, 2013).Interest rates on the contrary effect negatively private investment in MENA countries (Aysan et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of institutional FDI determinants in MENA countries was studied from different angles including the level of corruption in public administration (import and export licenses, money exchange, taxation, loans, etc.) and the investment conditions including contract enforcement, risk of expropriation and repatriation of profits (Helmy, 2013;Mohamed & Sidiropoulos, 2010). For instance, Inward FDI in Arab countries is negatively associated with the level of country risk (Moosa, 2009), and political instability (Salem & Baum, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%